Karakter Morfologi Buah Lima Varietas Pisang Lokal (Musa spp.) di Daerah Purwokerto dan Sekitarnya - Pratama, Afico Razaky; Yuniaty, Alice; Susanto, Agus Heri (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study characterizes the morphology and analyzes the phylogenetic relationships of five local banana varieties found around Purwokerto area, Central Java (wild, ulin, mas, raja, and ambon) by means of observation on nine qualitative traits and UPGMA (Unweighted Pair Group Method with Arithmetic Mean) analysis. The results reveal morphological variations among the five banana varieties, especially with respect to three main characters, i.e. fruit shape (curved/straight), presence of seeds (present/absent), and bunch surface (hairy/hairless). The wild banana exhibits typical wild morphological characteristics (angled seeds, hairy bunches), while the four cultivated varieties show domesticated features (seedless and hairless bunches). UPGMA analysis shows that ambon, raja, mas, and ulin cultivars are grouped into a single cluster, indicating morfological similarity and a possible close genetic relationship, while wild banana lies as an outlier, indicating sufficiently high morphological differences from the four cultivars.